Perceptions and practices of U.S. pre-service special education teachers on teaching social studies instruction in inclusive classrooms. Issue 8 (3rd July 2021) - Rodriguez, Jacqueline
ABSTRACT: In the most recent reauthorization of the seminal U.S. special education law, the Individuals with Disabilities Education Improvement Act (IDEIA), reaffirmed that students with disabilities should be taught in their least restrictive environment. This environment has progressively been seen as the general education classroom. The push for inclusion has resulted in a heightened sense of collaboration and co-teaching practices between general and special educators. Within general education settings, inclusion asks that special educators assume a more active, unified and participatory role in the design and delivery of content-based instruction. This study surveyed 179 preservice special education teachers through questionnaires regarding their practices and perceptions of teaching social studies in inclusive settings. The results indicate that preservice students lacked a cogent definition of social studies as well as exposure to effective instructional practices. Both deficits contributed to a general lack of confidence in their ability to teach social studies in general education settings. It was therefore recommended that preservice special educators take a social studies methods course which supports field-based exposure to co-planning and co-teaching collaborative opportunities.